2002
DOI: 10.1097/01.asn.0000034944.90425.75
|View full text |Cite
|
Sign up to set email alerts
|

Donor Hepatitis C Seropositivity

Abstract: Abstract. The impact of hepatitis C virus-positive donor kidneys on patient survival has not been analyzed in a national study. This study analyzed 20,111 adult (age, Ն16 yr) recipients having solitary cadaveric kidney transplants from adult donors with valid donor hepatitis C serologies from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 37 publications
8
52
1
Order By: Relevance
“…Its use is not recommended after renal transplantation due to a significant risk of graft loss. [20][21][22][23] Adverse consequences on long-term graft and patient survival related to the presence of HCV infection after kidney [24][25][26][27][28][29] and kidney-pancreas 30 transplantation have been clearly established. Thus, it is imperative that safe and effective therapy for chronic HCV infection be administered prior to renal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Its use is not recommended after renal transplantation due to a significant risk of graft loss. [20][21][22][23] Adverse consequences on long-term graft and patient survival related to the presence of HCV infection after kidney [24][25][26][27][28][29] and kidney-pancreas 30 transplantation have been clearly established. Thus, it is imperative that safe and effective therapy for chronic HCV infection be administered prior to renal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…More than half of DHCV+ kidneys are transplanted in HCV+ recipients in the United States; risk factors associated with DHCV+ kidney transplantation include advanced donor and recipient age, African American race, and the possibility of a high rate of dialysis access complications (1,2,4). In addition, DHCV+ kidneys may be used with substantial variation between or within transplant centers depending on circumstances impossible to capture in reviewing single-or multi-center experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published data confirmed that kidneys from donors who were hepatitis C positive (HCVϩ) were associated with an independently increased risk of death in renal transplant recipients regardless of recipient HCV status (1). However, donor hepatitis C seropositivity (DHCVϩ) was not independently associated with mortality when limited to patients with valid information (Centers for Medicare and Medicaid Studies [CMS] Form 2728) on comorbid conditions at the time of dialysis initiation.…”
mentioning
confidence: 99%